2018
DOI: 10.9775/kvfd.2018.19941
|View full text |Cite
|
Sign up to set email alerts
|

Tahıl Samanının in vitro Fermantasyon Özelliklerini Geliştirmede Se, Cr ve Zn İle Zenginleştirilmiş Maya Kültürünün Değerlendirilmesi

Abstract: The object of this study was to evaluate the effect of different sources and supplementation levels of yeast culture on in vitro fermentation characteristics of goats. The present study was performed in a 3×4 factorial design to examine the impacts of inclusion of three kinds of yeast culture (Se-enriched, Cr-enriched, Zn-enriched yeast culture) at four dose (0, 0.1%, 0.25%, 0.40% and 0.55%) on the in vitro fermentation characteristics of cereal straw. For maize stover, the results shown that the average value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In vitro true digestibility and IVTNDFD are an important parameter of evaluating the digestion of forage [46] . Oba and Allen [27] reported that a one-unit of enhanced NDF digestibility in vitro was associated with 0.17 of dry matter intake, 0.23 kg of milk yield, and 0.25 kg of 4% fat-corrected milk yield.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro true digestibility and IVTNDFD are an important parameter of evaluating the digestion of forage [46] . Oba and Allen [27] reported that a one-unit of enhanced NDF digestibility in vitro was associated with 0.17 of dry matter intake, 0.23 kg of milk yield, and 0.25 kg of 4% fat-corrected milk yield.…”
Section: Discussionmentioning
confidence: 99%